CARDIOTOXICITY AND USE OF HERBAL DRUGS- A REVIEW - Kancharlapalli, Shalini; Sweeya, Pisupati SR; Gandham, A. Priya Darshini; Chidrawar, Vijay R; Rao, V. Uma Maheswara (Asian Journal of Pharmaceutical Research and Development, 2014)
Cardiotoxicity is the occurrence of heart electrophysiology dysfunction and/or muscle damage. Acute myocardial infarction (MI), the most important consequence of cardiotoxicity, is the necrosis of a region of myocardium caused by an interruption in the supply of blood to the heart usually as a result of occlusion of a coronary artery. Evidence suggests that oxidative stress resulting from increased production of reactive oxygen species (ROS) may play a important role in the pathogenesis of myocardial infarction. There is evidence that antioxidants can protect against free radical defense, which is responsible for reperfusion-induced damage and thereby inhibit myocardial damage and arrhythmias during acute myocardial infarction. Various studies showed that the natural antioxidants have very less toxicity and proved to be safer and effective and they scavenge the free radicals and avoid excess ROS formation in the body thereby helping in mitigating cardiac diseases and several other disorders. Many herbal medicines have been reported to contain large amount of antioxidants. Many herbal drugs have observable beneficial actions on the heart serving as cardiotonics. Where in, digoxin (Lanoxinin) is even clinically prescribed for the treatment of congestive cardiac failure. Though herbal drug industry is growing at an astounding rate all over the world, their efficacy and safety is always questioned. There are only "evidence-based" medicine and "as-yet unproven" medicine, regardless of origin, conventionality or approach. Some of the herbal drugs which are good antioxidants, besides their use for cardiac insufficiency and other cardiac disorders are in turn responsible for causing potential cardiotoxic adverse effects. Thus, herbal products not regulated as medicines cannot be seen as alternative therapies unless they are shown to be equally effective as accepted agents.